Efficacy and Toxicity of Pegaspargase and Calaspargase Pegol in Childhood Acute Lymphoblastic Leukemia: Results of DFCI 11-001. Issue 31 (1st November 2021) - Vrooman, Lynda M.; Blonquist, Traci M.; Stevenson, Kristen E.; Supko, Jeffrey G.; Hunt, Sarah K.; Cronholm, Sarah M.; Koch, Victoria; Kay-Green, Samantha; Athale, Uma H.; Clavell, Luis A.; Cole, Peter D.; Harris, Marian H.; et al.
Abstract : PURPOSE: Dana-Farber Cancer Institute Acute Lymphoblastic Leukemia (ALL) Consortium Protocol 11-001 assessed efficacy and toxicity of calaspargase pegol (calaspargase), a novel pegylated asparaginase formulation with longer half-life, compared with the standard formulation pegaspargase. METHODS: Patients age 1 to ≤ 21 years with newly diagnosed ALL or lymphoblastic lymphoma were randomly assigned to intravenous pegaspargase or calaspargase, 2, 500 IU/m 2 /dose. Patients received one induction dose. Beginning week 7, pegaspargase was administered every 2 week for 15 doses and calaspargase every 3 week for 10 doses (30 weeks). Serum asparaginase activity (SAA) (≥ 0.1 IU/mL considered therapeutic) was assessed 4, 11, 18, and 25 days after the induction dose and before each postinduction dose. RESULTS: Between 2012 and 2015, 239 eligible patients enrolled (230 ALL, nine lymphoblastic lymphoma); 120 were assigned to pegaspargase and 119 to calaspargase. After the induction dose, SAA was ≥ 0.1 IU/mL in ≥ 95% of patients on both arms 18 days after dosing. At day 25, more patients had SAA ≥ 0.1 IU/mL with calaspargase (88% v 17%; P ˂ .001). Postinduction, median nadir SAAs were similar (≥ 1.0 IU/mL) for both arms. Of 230 evaluable patients, 99% of pegaspargase and 95% of calaspargase patients achieved complete remission ( P = .12), with no difference in frequency of high end-induction minimal residual disease among evaluable patients with B acute lymphoblastic leukemia (B-ALL). There were no differences in frequencies of asparaginase allergy, pancreatitis, thrombosis, or hyperbilirubinemia. With 5.3 years median follow-up, 5-year event-free survival for pegaspargase was 84.9% (SE ± 3.4%) and 88.1% (± SE 3.0%) for calaspargase ( P = .65). CONCLUSION: Every 3-week calaspargase had similar nadir SAA, toxicity, and survival outcomes compared with every 2-week pegaspargase. The high nadir SAA observed for both preparations suggest dosing strategies can be further optimized.